Les devoirs à la maison comme outil de partenariat éducatif : points de vue des élèves et de leurs parents - Daniel Jecker; Marc Weisser (Université de Provence, 2015)
Both the family and school share the responsibility for the education of children. However, the relationship between these two institutions is not always the most harmonious. A number of practices are designed to improve communication between them. This article focuses on one of these - homework. What is the reaction to the intrusion of school work into the family home ? We interviewed all the parents and students of a school within a working-class area. The results of the survey firstly reveal, according to the interviewer, that the recognized objectives of this educational practice differ, which obviously affects the way in which they are followed through. Secondly, the findings show that the vast majority of families willingly dedicate time for homework ; and finally, the results of the survey highlight that homework is one of the main methods of communication valued by parents.